Review of Energy Usage Patterns In India: - (Journal of Advances and Scholarly Researches in Allied Education, 2013)
Energy has been universally recognized as one of the mostimportant inputs for economic growth and human development. There is a strongtwo-way relationship between economic development and energy consumption. Onone hand, growth of an economy, with its global competitiveness, hinges on theavailability of cost-effective and environmentally benign energy sources, andon the other hand, the level of economic development has been observed to bedependent on the energy demand (EIA, 2006). Energy intensity is an indicator toshows how efficiently energy is used in the economy. The energy intensity ofIndia is over twice then that of the matured economies, which are representedby the OECD (Organization of Economic Co-operation and Development) membercountries. India’s energy intensity is also much higher than the emergingeconomies. However, since 1999, India’s energy intensity has been decreasingand is expected to continue to decrease (GOI, 2001).